Meningkatkan Kemampuan Menentukan Nilai Tempat Suatu Bilangan Dengan Metode Montessori Bagi Anak Tunarungu Kelas V Di SLB Negeri Aek Kanopan - Rita Purnama Sari; Grahita Kusumastuti (Jurnal Penelitian Pendidikan Khusus, 2023)
Â The current research was prompted by a problem reported by witnesses at SLB Negeri Aek Kanopan, where a small child from the deaf tribe had difficulty with a certain location. However, the aim of this study is to increase the capacity of using the Montessori method to determine specific locations.The current study uses a single subject research methodology (SSR) along with A-BA aesthetics and visual graphic analysis techniques. The frequency used by the variable type size. The data collection technique used is called a test, which provides about 20 items worth of information per unit of time. According to all study findings, the use of Montessori media can significantly increase the capacity to discover the abilities of deaf children. Each increase in ability is compared to the ability of the learner's first observer (A1) using oscillation frequencies 2, 4, 4, and 2. When the teacher intervenes using the Montessori method (B) six times, the frequency of students increases to 10, 13, 15, 18, 20, 20, and subjects experienced the highest frequency at the time of the intervention, namely 20, 20, 20, 20. The findings of this study support the idea that using the Montessori Method can increase a person's capacity to determine the location of a certain number